2008
DOI: 10.1111/j.1365-3059.2007.01747.x
|View full text |Cite
|
Sign up to set email alerts
|

Diplodia mutila causing seedling mortality of the palm Iriartea deltoidea

Abstract: Huelva in southern Spain is a major production area for strawberry ( Fragaria × ananassa ). At the end of the 2006 season (May-June) collapsed and dying strawberry plants were observed on several cultivars in four fields. Cut crowns of affected plants revealed dark brown necrotic areas on the margins and along the woody vascular ring. Roots of these plants were also shown to be necrotic. Macrophomina -like isolates developed from surface-disinfested affected tissues plated on potato dextrose agar amended with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…An additional experiment showed that pathogenicity of D. mutila increased with light availability. We inoculated 22 healthy 6-month old I. deltoidea seedlings (no foliar spots or insect marks) with D. mutila , following inoculation procedures from previous studies [25]. Foliar spots produced by D. mutila had a higher growth rate and mortality was greater and faster at higher light availability ( F 1,22  = 93.26, P  = 0.0001, r 2  = 0.816) (Fig.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…An additional experiment showed that pathogenicity of D. mutila increased with light availability. We inoculated 22 healthy 6-month old I. deltoidea seedlings (no foliar spots or insect marks) with D. mutila , following inoculation procedures from previous studies [25]. Foliar spots produced by D. mutila had a higher growth rate and mortality was greater and faster at higher light availability ( F 1,22  = 93.26, P  = 0.0001, r 2  = 0.816) (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…Diplodia mutila is frequently an asymptomatic endophyte in seeds, fruits, leaves of healthy juvenile and mature plants of I. deltoidea (88.4% infection of adult plants [29]) but can also act as a pathogen, causing mortality in young I. deltoidea seedlings after 5 to 16 days of infection and producing foliar spots in adult plants [25] (Fig. 5A–D).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…) and reported as the causal agent of seedling mortality of Iriartea deltoidea palm trees in Peru (Alvarez‐loayza et al. ). According to the pathogenicity test, Pm.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggest that damage decreases at high irradiance levels (Augspurger ), while other studies found that an increase in irradiance can increase damage by natural enemies (Alvarez‐Loayza et al . ). The effect of abiotic factors may vary with traits of the host species; for example, drought may increase vulnerability to natural enemies in drought‐intolerant, but not drought‐tolerant species (Fine, Mesones & Coley ).…”
Section: Introductionmentioning
confidence: 97%